Implementation Security Certification of Decoy‐BB84 Quantum Key Distribution Systems. Issue 5 (14th May 2019) - Tomita, Akihisa
Abstract: One of the most important obstacles for the social deployment of Quantum Key Distribution (QKD) systems is the lack of standards for security certification. Proper selection of application will circumvent other obstacles, such as cost, key generation distance, and rate. Nevertheless, security certification of real systems, or "implementation security certification" is indispensable. Such certification should be clear and tractable for non‐experts and should be performed with standardized characterization methods. Otherwise, the potential users cannot adopt the QKD system with confidence, because the highest level of security is what QKD appeals. This report discusses the process of the implementation security certification and the requirements for device characterization. It also presents several case studies on the requirements and experimental characterization of QKD devices for the security certification. Abstract : Quantum key distribution (QKD) technologies have been matured to apply real world networks. However, implementation security certification is indispensable for the social deployment. This report provides a framework of security certification on implemented QKD devices by discussing test items, methods, and criteria. Several case studies on the characterization and improvement of QKD devices for the security certification are presented.